(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Report of research experience carried out at the Summer Seminar Writing (about/on/with/at/the) Contemporary Circus, at Concordia University, Montreal-CA. The experience consisted of submitting a circus performer with good command of her modality, but without street circus experience, to three forays into a public space. After each foray, the artist had the collaboration of an experienced street artist to readjust her presentation. Without intending to offer an instruction manual or determine ways of acting, we seek to develop reflections that can articulate theory with practice, bringing some articulations of the praxis of the street circus.